A genealogy of Marion's philosophy of religion : apparent darkness - Jones, Tamsin, 1974- (Indiana series in the philosophy of religion., 2011)
Tamsin Jones believes that locating Jean-Luc Marion solely within theological or phenomenological discourse undermines the coherence of his intellectual and philosophical enterprise. Through a comparative examination of Marion's interpretation and use of Dionysius the Areopagite and Gregory of Nyssa, Jones evaluates the interplay of the manifestation and hiddenness of phenomena. By placing Marion against the backdrop of these Greek fathers, Jones sharpens the tension between Marion's rigorous method and i.